Verb Phrase and Its Translations Found in the Novel “Budha, a Story of Enlightenment” - I Made Juliarta (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This study aims at analyzing the syntactic structure of the verb phrase and its translation process occurred.  This study also analyzes the kinds of shifts of verb phrase occurred in the translation process from English into Indonesia.  This study is a descriptive qualitative study.  The theory used in analyzing data is the theory proposed by Catford and Radford (1988). The theory used in analyzing the data source is the theory in translation especially in shifts of translation and the theory in syntax in order to analyze the verb phrases found in the data source. There are 12 verb phrases as data of this study. The verb in the data source can be categorized as an Indonesian verb. It can be seen from the text that is available in the data source, that the verb phrase in the source language can be transferred into an Indonesian verb in the target language Then, there are some steps applied in this study, the first step of this research is to collect the data source found in the novel The Budha, a Story of Enlightenment. The second step is to read and identify the text in the novel The Budha, a Story of Enlightenment containing the verb phrase. The next step is to take some texts, analyze and interpret the data, and finally draw a conclusion. The verb phrase found in the novel The Budha, a Story of Enlightenment was identified by the researcher. And this study continued in analyzing the translation process occurred. The result of translation analysis of the text shows that there is a shift occurred in all the 12 processes of translating English verb phrase into Indonesian. 8 are classified as changing into lower rank and 4 are classified as changing into a higher rank.